The Bright Side of Social Media: Social Media Platforms Adoption and Start-Up Sustainability - Mujahid, Muhammad Saeed; Mubarik, Muhammad Shujaat (Frontiers in Psychology, 2021)
This study aims to explicate the contribution of social media platforms adoption on start-up sustainability. Since most economies of the world start-up failure rate are relatively high, there is always a desire or a need to investigate the success recipe. As a result, the primary objective of this study is to understand the social media environment and how start-ups can best utilize social media platforms throughout their life cycle. Based on the qualitative case study approach, five in-depth interviews of social media marketers and individuals working in start-ups were conducted. The finding demonstrates that social media is a crucial virtual platform for striving resource start-ups. Therefore, if a platform gets utilized correctly, it can play an essential role in the sustainable progression of a start-up. Thus, there is a need for start-ups to articulate a comprehensive social media policy for each life cycle stage.